Teknik Evaluasi Non Tes - Eti Shobariyah (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2018)
Evaluation is important in a learning process because evaluating teachers, students and other educational stakeholders can find out how far the learning is successful. Many think that the evaluation is only done through tests, even though there are other techniques in evaluating learning or also other activities namely through Non-Test Evaluation. Non-test evaluation is an assessment technique that is carried out without using a test. So that this technique is done through careful observation and without testing students. Non-test evaluation is different from test evaluation if the evaluation is often only used to measure a person's level of knowledge, but instead, non-test evaluation is an evaluation technique to measure, assess and conclude the evaluation results are not based on the instrument on the questions. The use of non-test evaluation is usually used more to the affective and psychomotor aspects of a person or a student. Non-Test Evaluation includes Interview, Observation, Questionnaire, Project Work, Tiered Scale, and Performance.